Implementation evaluation of a school- and primary care-based multicomponent intervention to improve HPV vaccine coverage: Results from the PrevHPV randomized controlled trial - Aurélie Bocquier; Maïa Simon; Morgane Michel; Stéphanie Bonnay; Isabelle Adam; Serge Gilberg; Sébastien Bruel; Aurélie Gauchet; Anne-Sophie LeDuc-Banaszuk; Amandine Gagneux-Brunon; Judith E. Mueller; Bruno Giraudeau; et al. (Journal of Infection and Public Health)
Background: Human papillomavirus (HPV) vaccine coverage (VC) remains lower than expected in France. The PrevHPV national research program aimed to codevelop and evaluate an intervention including three components: ‘education and motivation’ of adolescents in schools, ‘at-school vaccination’, ‘general practitioners (GPs)’ training’. This study aimed to evaluate the implementation outcomes of each component, whether they affected effectiveness, and identify factors influencing implementation in schools. Methods: A mixed-method study embedded in a cluster randomized controlled trial in 91 French municipalities (July 2021-June 2022). Quantitative data were collected through activity reports and questionnaires, and qualitative data through focus groups with school staff. The implementation outcomes were fidelity, dose, reach, acceptability and sustainability, as defined in the Medical Research Council guidance for process evaluation of complex interventions and Proctor et al.’s Implementation Outcomes Framework; the effectiveness outcome was HPV VC (≥ 1 dose) two months after the end of the intervention. Qualitative data were analyzed using the Consolidated Framework for Implementation Research. Results: The fidelity, acceptability, and sustainability of all three components among participants who completed the intervention were high. However, the withdrawal of one-third of schools before the trial started and difficulties in mobilizing GPs negatively impacted the dose and reach outcomes. Estimates for the on-treatment analyses of the effectiveness were greater than those for which the dose of intervention received was not considered; ‘at-school vaccination’ (11.25 percentage points, p < 0.001) and ‘GPs’ training’ (3.56 percentage points, p = 0.049) increased VC, while ‘education and motivation’ remained nonsignificant. Conclusions: Increasing HPV VC among adolescents could be achieved by combining interventions in both schools and primary care settings. This study provides practical implications for implementing such interventions in real life. Trial registration: Clinicaltrials.gov, NCT 04945655. Registered 30 June 2021, https://clinicaltrials.gov/study/NCT04945655